A Phase I Dose-Escalation/Expansion Study of Fractionated-Dose and Multiple-Cycle Anti–PSMA-Targeted α-Emitter 225Ac-J591 in Patients with Prostate Cancer - Scott T. Tagawa; Charlene Thomas; Abdul Baseet Arham; Aaron Holmes; Valentina Marulanda Corzo; Tobechukwu Okobi; Shankar Vallabhajosula; Vasilios Avlonitis; Sandra Huicochea Castellanos; Jones T. Nauseef; Elisabeth O’Dwyer; Maham Fatima; et al. (Clinical Cancer Research, 2026)
Abstract Purpose: To test the safety of two regimens at differing levels of radioactivity of prostate-specific membrane antigen (PSMA)–targeted α-radionuclide 225Ac-J591. Patients and Methods: Patients with progressive, metastatic androgen pathway modulation–resistant prostate cancer were enrolled in two parallel dose-escalation cohorts: (i) fractionated-dose regimen (single cycle of 45–65 KBq/kg of 225Ac-J591 on days 1 and 15; main cohort agnostic to prior receipt of 177Lu-PSMA and an additional cohort with prior receipt of 177Lu-PSMA) and (ii) multiple cycles of 225Ac-J591 (45–65 KBq/kg administered every 6 weeks for up to 4 cycles). PSMA PET was not utilized for eligibility. The primary endpoint was determination of dose-limiting toxicity (DLT) and recommended phase II dose (RP2D); the fractionated cohort was expanded. Results: Forty-two patients were enrolled in the fractionated-dose regimen (23 dose-escalation, 11 dose-expansion, and 8 after 177Lu-PSMA) and 18 in multiple-dose regimen. All received ≥1 prior androgen receptor pathway inhibitor, 72% received chemotherapy, and 18% received 177Lu-PSMA. Three patients had DLTs in the fractionated regimen with RP2D of 60 KBq/kg twice. Seven had DLTs in the multiple-cycle regimen; this regimen is not recommended for further development. Among adverse events of special interest, temporary hematologic toxicity was most common [93% thrombocytopenia (32% grade >3), 65% neutropenia (13% grade ≥3), and 63% anemia (20% grade ≥3)]; dry mouth occurred in 62% (2% grade 2). Across fractionated cohorts with or without prior 177Lu-PSMA, a >50% prostate-specific antigen (PSA) decline was the best response occurring in 60% of patients; 28% had a >50% PSA decline in multiple cycles. Conclusions: Fractionated dosing of 225Ac-J591 seems promising. Further investigation is underway.